I-Ta’am platform – Connecting food makers, consumers and charity organizations seamlessly - Hamood Al-Ansi, Maha Abdulmalek; Rukhsana, Rubaite; Ahmad Dahlan, Abdul Rahman (Research Publish Journal, 2018)
The objective of this paper is to propose a platform that linking between food providers such as restaurants, chefs, food tracks, homemakers and customers individuals looking for nearby food. The I-Ta’am is a Consumer-to-Customer (C2C) business model which aims to provide a conceptual solution of purchasing and vending foods. Nine blocks of Business Model Canvas (BMC) framework, Literature Review, strategy canvas, value proposition design (VPD) and environmental map,e-commerce have been used as the methodologies for this paper.